Screening of depression and anxiety in adolescents with cystic fibrosis and caregivers in Turkey by PHQ-9 and GAD-7 questionnaires - KARADAĞ, BÜLENT TANER; YILMAZ YEĞİT, CANSU; ERDEM ERALP, ELA; GÖKDEMİR, YASEMİN (WILEY, 2021)
Background Depression and anxiety symptoms in patients with cystic fibrosis (CF) and their caregivers are 2-3 times higher than in the normal population. This study aims to evaluate the frequency and severity of depression and anxiety symptoms and to determine possible risk factors in CF patients and their mother and/or fathers at Marmara University CF center. Methods The study included 132 CF patients who were followed up at our CF center. Patient Health Questionnaire (PHQ-9) and the Generalized Anxiety Disorder Questionnaire (GAD-7) were used to screen depression and anxiety. The questionnaires were completed by 50 CF patients (aged 12-17 years) and 132 parents of patients (aged 0-17 years). Results While moderate to severe depressive symptoms were seen in 26% of patients, 33.7% of mothers and 14.6% of fathers; moderate to severe anxiety were present in 18%, 21.8% and 8.5%, respectively. None of the demographic characteristics was identified as a predictor of depression or anxiety. GAD-7 scores have shown a higher prevalence of anxiety in mothers of patients with chronic methicillin-resistant Staphylococcus aureus (p = .034). Additionally, hospitalization in the last 12 months was significantly correlated with higher PHQ-9 scores in fathers (p = .043). Analysis of patients' adherence to medical treatment and airway clearance showed higher depression and anxiety in mothers of the nonadherent group (p = .002). Conclusion Depression and anxiety were common in CF patients and their parents. These results illustrate the importance of depression/anxiety screening and psychosocial support for the CF patient and their parents.
Keywords: anxiety; cystic fibrosis; depression; GAD‐ 7; PHQ‐ 9